MENGANALISIS DALIL TENTANG KEESAAN ALLAH SWT:STUDI INTEGRASI ARGUMEN RASIONAL (DALIL AQLI) DAN TEKSTUAL (DALIL NAQLI) - Bayu Bambang Nurfauji; Tiara Khoirunisa; Mila Nuriyah; Arid Burhanudin; Zaidan Ibnu Arifin; Kholisoh Fikriyah (Adisam Publisher, 2026)
Rational evidence (dalil aqli) and textual evidence (dalil naqli) are two important pillars in the structure of Islamic thought, serving as the foundation for understanding religious teachings, whether in terms of creed, law, or ethics. Textual evidence comes from God’s revelation recorded in the Qur’an and the Hadith of Prophet Muhammad (peace be upon him), whereas rational evidence comes from the human intellect granted by God as a means to think, reflect, and draw conclusions. Both play interrelated roles and cannot be separated in the process of establishing legal rulings and strengthening religious beliefs. This aims to examine the meaning, position, and functions of aqli arguments and naqli arguments, as well as to explain the relationship between the two from the perspective of Islamic thought. The method used is library research with a descriptive-analytical approach to relevant primary and secondary sources, both from classical and contemporary literature. Textual evidence (dalil naqli) occupies the primary position as the source of absolute truth, while rational evidence (dalil aqli) functions as a supporting instrument in understanding, interpreting, and explaining the content of textual evidence in a rational and contextual manner. When used proportionally, rational evidence will not contradict textual evidence, but rather strengthen the understanding of Islamic teachings. Therefore, the integration of rational and textual evidence becomes very important in developing a balanced, rational Islamic thought that remains based on revelation